The influence of digital out-of-home media on driver perception and driving: an integrative literature review - Lima Felisberto, Lara; Casarin, Vanessa (InfoDesign, 2024)
Out-of-home Media is constantly changing, incorporating new technologies, such as digital technology; this media is advancing faster than the research on the effects of it on consumers and the government in regulating it. In this sense, in order to contribute to advances in research and production within Information Design, we sought to investigate the influence of digital out-of-home (DOOH) media on driver perception and driving, striving to answer three main questions: What is the influence of DOOH Media on driving? What guidelines may be found in the scientific literature for managing these media in the landscape? What are the suggestions for future studies in this field? Research procedures involved an integrative literature review to uncover research and advances in the field of digital out-of-home (DOOH) media indexed in recognized databases which resulted in the full text analysis and synthesis of 32 studies, considering papers in scientific journals, conference papers, PhD thesis and research reports. The results pointed out that digital advertisements, especially animated ones, catch the attention of drivers and may compromise road safety. The distraction level may be affected depending on the luminance, brightness, and contrast levels and the number of words on the screen. Also, it was observed that young and senior drivers are more susceptible, and gender differences influence the perception and attention to the advertisements, although they are inconclusive. Studies recommend limiting words, controlling luminance, and adequately placing the advertisements for regulation.